The Oxidation of Fe (II), Fe (II) Mineral, and Rapid Denitrification under Cyanobacterial Interfacial Competition by Novel NDFe(II)OB, Pseudogulbenkiania ferrooxidans sp. MAI-1 - Robinson, Bryce (Université d'Ottawa / University of Ottawa, 2019)
Nitrogen is an essential constituent and building unit of all living organisms, and the primary limiting nutrient on our planet such that its cycle widely depends on the diverse nitrogen-transforming microorganisms, such as denitrifiers. Oxygen minimum zones or hypoxic aquatic ecosystems account for 30-50% of all nitrogen denitrification and under dynamic transformation imbalance, of measure dependent variable modularity, little is known about discrete shifts in denitrification competition by various microorganisms of divergent metabolism; or the Fe (II) – Fe (III) redox linking process. Novel nitrate dependent Fe (II) oxidizing bacteria as rapid denitrifier and iron oxidizer can significantly oxidize various iron minerals (magnetite and ferrous mono sulfide). Evidence of nitrate dependent Fe (II) oxidation by the bacterium P. ferrooxidans sp. MAI-1 could shed light as a novel competitor at microaerophilic (<2.0mg/L DO, -100 – +100 mV) interfacial competition with cyanobacteria Microcystis aeruginosa corollary to ecosystem eutrophication and concomitant microcystin production, with the goal of abating a toxic cyanobacterial bloom. Nitrate Dependent Iron Oxidizing Bacteria (NDFe(II)OB) showed rapid nitrate reduction (>25 mg/L NO2, day 7) and consequent bright-orange iron oxides. Saturation indices (day 1 and 8 SI = log (IAP/Ksp), showed non exclusive vivianite formation i.e., 3.80 and 0.44-0.55, respectively, with near complete oxidation by day 8, significantly abating logarithmic growth over a fourteen day period (p>0.01). N-N dichotomies are not purely exclusive, as terminal PO4 competition differed by ~0.1 mg/L after a 15 day period, with approximately one five hundred times more N-nitrogen loss compared to P-phosphorus loss difference. Early logarithmic cyanobacteria cell counts under the presence of the competitor decreased by >20% by day 18 of growth. This is consistent with the classical view that under primary metabolite exhaustion, interspecific competition should lead to competitive exclusion and not niche differentiation.
Keywords: cyanobacteria; nitrate dependent iron oxidizer